Using Machine Learning Techniques to Develop Risk Prediction Models for the Risk of Incident Diabetic Retinopathy Among Patients With Type 2 Diabetes Mellitus: A Cohort Study - Zhao, Yuedong; Li, Xinyu; Li, Shen; Dong, Mengxing; Yu, Han; Zhang, Mengxian; Chen, Weidao; Li, Peihua; Yu, Qing; Liu, Xuhan; Gao, Zhengnan (Frontiers in Endocrinology, 2022)
Objective: To construct and validate prediction models for the risk of diabetic retinopathy (DR) in patients with type 2 diabetes mellitus. Methods: Patients with type 2 diabetes mellitus hospitalized over the period between January 2010 and September 2018 were retrospectively collected. Eighteen baseline demographic and clinical characteristics were used as predictors to train five machine-learning models. The model that showed favorable predictive efficacy was evaluated at annual follow-ups. Multi-point data of the patients in the test set were utilized to further evaluate the model’s performance. We also assessed relative prognostic importance of the selected risk factors for DR outcomes. Results: Of 7943 collected patients, 1692 (21.30%) developed DR during follow-up. Among the five models, the XGBoost model achieved the highest predictive performance with an AUC, accuracy, sensitivity and specificity of 0.803, 88.9%, 74.0% and 81.1%, respectively. The XGBoost model’s AUCs in different follow-up period were 0.834 to 0.966. In addition to the classical risk factors of DR, serum uric acid (SUA), low density lipoprotein cholesterol (LDL-C), total cholesterol (TC), estimated glomerular filtration rate (eGFR) and triglyceride (TG) were also identified to be important strong predictors for the disease. Compared with the clinical diagnosis method of DR, the XGBoost model achieved an average of 2.895 years prior to the first diagnosis. Conclusion: The proposed model achieved high performance in predicting the risk of DR among patients with type 2 diabetes mellitus at each time point. This study established the potential of the XGBoost model to facilitate clinicians identifying high-risk patients and making type 2 diabetes management-related decisions.